THE VALLEY OF THE SHADOW OF DEATH (Imaginations: Journal of Cross-Cultural Image Studies, 2013)
“The Valley of the Shadow of Death” is a brief meditation on the refraction of sunsets over desolated landscapes, photography of war, and the viewer’s relationship to the death of the sublime. The essay references the Museum of Fine Arts Houston exhibition “WAR/PHOTOGRAPHY: Images of Armed Conflict and Its Aftermath” (2012-13) citing one of Roger Fenton’s famous manipulated pictures from the Crimean war (1856) showing an empty landscape with cannonballs.